FACTOR ANALYSIS OF NON-MUSLIM CUSTOMERS IN SAVING AT SHARIA BANK OF INDONESIA BANDA ACEH BRANCH - Nabilla, Shinta; Ahmad, Kamaruzzaman Bustamam; Makinara, Ihdi Karim (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2024)
This research aims to analyze the factors that influence non-Muslim customers interest in saving at the Bank Syariah Indonesia BandaAceh Branch. With a background as a province with a majority Muslim population and the implementation of sharia law, Aceh provides its own challenges for non-Muslim customers in choosing financial institutions. This research covers factors such as regulatory policies, social norms, and the availability of Islamic banking services that influence the decision of non-Muslim customers to choose Bank Syariah Indonesia. The research method used is qualitative through the preparation and distribution of questionnaires distributed to non-Muslims as customers of Bank Syariah Indonesia. The results of this study there are several factors that cause non-Muslim customers to choose Bank Syariah Indonesia over other Islamic banks, namely non-Muslim customers in Banda Aceh tend to prefer Bank Syariah Indonesia (BSI) because of the affordability of location, attractive product promotions, quality service, and aspects forced by government regulations. These factors influence the decision of non-Muslim customers in choosing BSI as the first choice for their banking needs in the area.